chariots of the gods? : unsolved mysteries of the past - Daniken, Erich Von; Erich Von Daiken (Great, Britain Putnam's Sons, 1968)
Did spacemen visit earth thousands of years ago? we now have a proof! Because we find electric batteries many thousands of years old. Because we find strange beings in perfect space suits with platinum fasteners. Because we find numbers with fifteen digits- something not registered by any computer - but how did these early men acquire the ability to create them? Archeology accepts such mysteries as puzzles. And stops cold. Religion relate stories of gods who appeared with promises of a better life, only to use ultra-sophisticated weapons to destroy the people on earth. Now we are actually in a new space age. We have landed on the moon. With our new knowledge, we can re-examine history and begin to solve the puzzles of the past, with the evidence clearly before us of accomplishments and "miracles" impossible to have been achieved by primitive men. What were the fiery chariots that brought "gods" to earth? Could they have been spaceships from one of the billions of starts capable of supporting life long before the earth was cool?
English